A super hydrophobic fabric and its preparation method and application

The immersion-drying method loads the modified cellulose nanocrystals and silicone film layers on the fabric surface, which solves the problem of complex and high cost in the preparation of superhydrophobic surfaces in the prior art, and achieves stable superhydrophobic fabric preparation, with excellent durability and breathability.

CN116446182BActive Publication Date: 2025-04-25SUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310308129.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-27
Publication Date
2025-04-25
Estimated Expiration
2043-03-27

AI Technical Summary

Technical Problem

The prior art In preparing superhydrophobic surfaces, the process is complex and costly, and the widely used inorganic nanoparticles are expensive and may cause environmental pollution.

Method used

Superhydrophobic fabrics are prepared by impregnation-drying method. By loading the modified cellulose nanocrystals on the surface of the fabric and forming a hydrophobic coating with the silicone film layer, the rough morphology of the cellulose nanocrystals and the low surface energy of the silicone are used to achieve superhydrophobic function.

Benefits of technology

It is realized that the stable superhydrophobic fabric is prepared by a simple impregnation-drying method, which has excellent chemical durability, mechanical stability and good breathability, and the production method is simple and easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116446182B_ABST
    Figure CN116446182B_ABST
Patent Text Reader

Abstract

The present invention discloses a super-hydrophobic fabric and its preparation method and application. The super-hydrophobic function is achieved by modifying cellulose nanocrystals in cooperation with an organosilicon waterproofing agent. The hydrophobic performance of the fabric is particularly excellent and the preparation method is simple. First, cellulose nanocrystals are modified with heptadecafluorodecyltrimethoxysilane, and the modified cellulose nanocrystals are dispersed in a solution containing hydroxy silicone oil and hydrogen silicone oil; cotton fabric is taken out after being immersed, and then dried to obtain a super-hydrophobic fabric; the surface super-hydrophobic layer is composed of modified cellulose nanocrystals in cooperation with organosilicon, and the fabric finished with silicone oil containing modified CNCs shows perfect super-hydrophobicity, with a contact angle of 169.3° and a rolling angle of 4.9±0.1°. The fabric finishing process of the present invention is completed at room temperature, the production and preparation process is simple, the reaction conditions are mild, the operation is safe, and it is easy to scale up production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a super-hydrophobic fabric and a preparation method thereof. Specifically, the super-hydrophobic fabric is prepared by an impregnation method, and the fiber surface layer of the super-hydrophobic fabric obtained by impregnation is a modified cellulose nanocrystal coordinated organic silicon coating. The invention belongs to the technical field of functional textiles and preparation methods thereof. Background Art

[0002] Cellulose is formed by plants through photosynthesis, and it is the most basic skeleton material for all plants. Cellulose is a natural polysaccharide polymer. Countless cellulose polymer chains are intertwined and arranged in relative order to form cellulose fibers. The hydroxyl groups in the cellulose polymer chain are combined with the hydrogen atoms on the hydroxyl groups in the adjacent polymers in the form of hydrogen bonds to form a compact crystalline region. Only a few amorphous regions exist in the cellulose fibers. Cellulose nanomaterials are natural polymer materials. Unlike inorganic nanomaterials, which generally have stable and single chemical molecular composition and structural form, cellulose nanomaterials have a variety of properties and structures. It is not just a simple "nano" of the physical size of cellulose fibers. At the same time, because its polymer morphology and molecular weight have also changed greatly, its performance has far exceeded the performance of cellulose itself, and the activity of functional groups has also been enhanced.

[0003] In the context of sustainable development, the research of super-hydrophobic surfaces with low cost and environmental protection has attracted increasing interest in the scientific community. However, the practical application of super-hydrophobic surfaces is still hindered by the complex preparation process and high cost. Constructing super-hydrophobic surfaces by imitating the "lotus effect" is a research hotspot in materials science. Usually, nanoparticles (ZnO, SiO2, TiO2, carbon nanotubes) are fixed on the surface of the substrate through various methods such as sol-gel, electrospinning and 3D printing to construct super-hydrophobic surfaces. However, the widely used inorganic nanoparticles are not only expensive, but also may cause environmental pollution. Summary of the invention

[0004] The present invention adopts an immersion-drying method to prepare a super-hydrophobic surface. Fabric is selected as a base material, and modified cellulose nanocrystals are loaded on the surface of the fabric. First, silane is grafted on the surface of the cellulose nanocrystal through a chemical reaction, and dispersed in an organosilicon treatment liquid to form a fabric finishing liquid. After the fabric is impregnated with the finishing liquid, it is heated and cured in an oven to obtain a super-hydrophobic fabric. This method only uses a simple immersion-drying method to prepare a cellulose nanocrystal-fiber composite material, and the fiber and the nanoparticles are connected by covalent bonds and are very stable.

[0005] The technical solution for achieving the purpose of the present invention is:

[0006] A super-hydrophobic fabric comprises a fabric and a surface finishing layer thereof, wherein the finishing layer comprises a modified cellulose nanocrystal roughening layer and an organosilicon film layer. The super-hydrophobic fabric of the present invention has a substrate of a cellulose fiber-based fabric, including cotton, linen, regenerated cellulose fiber-based fabric or a blended fabric of any two of the above; the surface finishing layer of the fabric is composed of modified cellulose nanocrystals and organosilicon, and the super-hydrophobic fabric is formed by the cellulose nanocrystals through the joint action of constructing a rough morphology and a low surface energy substance.

[0007] The present invention uses an impregnation-drying strategy to prepare a super-hydrophobic surface, selects fabric as a cellulose fiber base material, and the base material and the cellulose nanocrystal interface are firmly bonded. The present invention constructs a "roughened" morphology on the surface of the cellulose-based fabric by using modified cellulose nanocrystals, and forms a hydrophobic coating with an organic silicon film. The coating structure is shown below:

[0008]

[0009] Wherein, R1 includes tridecafluorooctyl, heptadecafluorodecyl, octadecyl, and hexadecyl; m represents a repeating unit, and is preferably 20 to 200.

[0010] In the super hydrophobic fabric of the present invention, modified cellulose nanocrystals are loaded on the surface of the fabric fibers. Due to the existence of van der Waals force between the cellulose nanocrystals and the cellulose fiber substrate, the cellulose nanocrystals are aggregated and coated on the fiber surface, greatly increasing the roughness of the fabric surface. The improvement of the fiber surface roughness cooperates with the low surface energy of the organic silicon in the surface film layer to provide a super hydrophobic function.

[0011] In the present invention, the cellulose nanomaterial has renewability, low density, biocompatibility and degradability. The cellulose nanomaterial also has high specific strength and high specific surface area. There are a large number of hydroxyl groups on the surface of the cellulose nanomaterial. Based on these hydroxyl groups, chemical modification can be performed to prepare functional materials with excellent performance. The modified cellulose nanocrystals are fluorinated silanes or fluorinated silane-free cellulose nanocrystals; the organosilicon includes hydrogen silicone oil and hydroxy silicone oil. Preferably, the fluorinated silane includes one or more of tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, and heptadecafluorodecyltriethoxysilane; the fluorinated silane includes one or more of octadecyltrimethoxysilane, octadecyltriethoxysilane, hexadecyltrimethoxysilane, or hexadecyltriethoxysilane. The mass ratio of fluorinated silane or fluorinated silane to cellulose nanocrystals is (2-8):1, preferably (4-6):1.

[0012] The invention discloses a method for preparing the super-hydrophobic fabric. The super-hydrophobic fabric is obtained by dipping the fabric into a solution containing modified cellulose nanocrystals and organosilicon, then taking the fabric out and drying it.

[0013] In the present invention, modified cellulose nanocrystals are dispersed in an organosilicon treatment liquid to obtain a solution containing modified cellulose nanocrystals and organosilicon; the organosilicon treatment liquid includes hydrogen-containing silicone oil, hydroxy silicone oil, solvent, and catalyst; the modified cellulose nanocrystals are added to the organosilicon treatment liquid in the form of a modified cellulose nanocrystal dispersion. The mass ratio of the terminal hydroxyl silicone oil to the hydrogen-containing silicone oil is (0.5-5):1, preferably (1-2):1. The amount of modified cellulose nanocrystals, hydrogen-containing silicone oil and hydroxy silicone oil and the volume ratio of the solvent are (0.01-0.1) g: (0.1-0.5) g: 50 mL, preferably (0.03-0.06) g: (0.2-0.4) g: 50 mL.

[0014] As an example, the preparation method of the super hydrophobic fabric of the present invention comprises the following steps:

[0015] (1) adding a silane coupling agent (containing or not containing fluorine) to an ethanol / water mixture, adjusting the pH, and then adding cellulose nanocrystals, stirring and reacting for a certain period of time; after the reaction is completed, centrifuging and collecting the modified cellulose nanocrystals obtained by the reaction, and washing with ethanol to remove excess unreacted silane coupling agent;

[0016] (2) taking hydroxy silicone oil and hydrogen silicone oil, together with a catalyst, and dispersing them in an anhydrous alcohol solvent to form an organosilicon treatment liquid; then adding the above-mentioned modified cellulose nanocrystals and stirring to form a uniform dispersion; then immersing the fabric in the above-mentioned dispersion for a certain period of time, taking it out and drying it in an oven to completely remove the alcohol solvent, thereby obtaining a super-hydrophobic fabric; preferably, repeating the immersion-drying process is conducive to completely covering the surface of the fabric with the silicone oil-modified cellulose nanocrystal coating.

[0017] In the present invention, in step (1), the time for grafting modification (stirring reaction) of cellulose nanocrystals is 1 to 8 hours, preferably 5 to 7 hours; in step (2), the time for impregnation is 5 seconds to 60 minutes, preferably 10 seconds to 5 minutes, and most preferably 10 seconds to 60 seconds, and the impregnation time refers to the time of each impregnation; the number of impregnations is 1 to 10 times, preferably 2 to 5 times, and correspondingly, the number of dryings is 1 to 10 times, preferably 2 to 5 times.

[0018] In the present invention, the impregnation is carried out under stirring; preferably, after the impregnation-drying, thermal curing is carried out to obtain the super hydrophobic fabric.

[0019] In the present invention, the alcohol solvent used in the organic silicon treatment liquid is any one of methanol, ethanol, isopropanol or a mixture of any two thereof, and the catalyst is any one of dibutyltin dilaurate, tin acetylacetonate, and manganese acetylacetonate; the amount of the catalyst accounts for 1% to 5% of the total mass of the silicone oil.

[0020] The method of the present invention only uses a simple impregnation-drying method, selects fabric as the base material, grafts groups on the surface of cellulose nanocrystals through chemical reactions, and disperses them in silicone low surface energy materials. After the cotton fabric is impregnated, it is cross-linked and cured in an oven to obtain a super-hydrophobic fabric.

[0021] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0022] 1. On the fiber surface of super-hydrophobic fabrics, the cellulose fibers and cellulose nanocrystal particles are firmly bonded, and the silicon functional groups connected to the surface of the cellulose nanocrystal particles can be bonded to the outermost silicone coating through covalent bonds. The combination is very stable, so the finished fabric is washable.

[0023] 2. The super-hydrophobic fabric prepared by the present invention combines the unique advantages of softness and breathability, large specific surface area, porosity, and adjustable structural performance of the fabric, which is of great significance for improving the wearing performance, multifunctionality, and added value application prospects of the fabric.

[0024] 3. The super-hydrophobic fabric prepared by the present invention has excellent chemical durability and mechanical stability, which is very important for finishing fabrics for use in harsh environments.

[0025] 4. The present invention prepares super hydrophobic fabrics by a simple impregnation-drying process, the production method is simple, the reaction conditions in the production process are mild, the operation is easy, and the large-scale production and promotion are possible. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a diagram of the preparation process of superhydrophobic fabric.

[0027] Figure 2 This is a scanning electron microscope (SEM) image of raw cotton fabric with wrinkles on the surface.

[0028] Figure 3 The following are scanning electron microscope (SEM) images of unmodified cellulose nanocrystals (A) and scanning electron microscope (SEM) images of modified cellulose nanocrystals in Example 1 (B).

[0029] Figure 4 This is a scanning electron microscope (SEM) image of cotton fabric after silicone oil finishing (addition of modified cellulose nanocrystals) in Example 1.

[0030] Figure 5 It is the water contact angle (WCA) value of the cotton fabric after silicone oil finishing (addition of modified cellulose nanocrystals) in Example 1.

[0031] Figure 6 This is the EDS of cotton fabric after silicone oil finishing (addition of modified cellulose nanocrystals) in Example 1.

[0032] Figure 7 This is the mechanical stability test of cotton fabric after silicone oil finishing (adding modified cellulose nanocrystals) in Example 1: sandpaper wear test process (a) and the picture of the change of contact angle with wear cycle (b); tape peeling test process (c); the trend of contact angle change with adhesive cycle (d).

[0033] Figure 8 This is a scanning electron microscope (SEM) image of cotton fabric after silicone oil finishing and addition of modified cellulose nanocrystals in Example 2.

[0034] Fig. 9 It is the water contact angle (WCA) value of the cotton fabric after silicone oil finishing and addition of modified cellulose nanocrystals in Example 2.

[0035] Fig.10 It is the water contact angle (WCA) value of the cotton fabric after silicone oil finishing and addition of modified cellulose nanocrystals in Example 3.

[0036] Fig.11 This is a scanning electron microscope (SEM) image of the cotton fabric after silicone oil treatment in Comparative Example 1.

[0037] Fig.12 It is the water contact angle (WCA) value of the cotton fabric after silicone oil treatment in Comparative Example 1.

[0038] Fig.13 The contact angle changes of the fabric after finishing with different silicone oil ratios: the amount of terminal hydroxyl silicone oil is fixed at 0.2 g (a); the amount of hydrogen-containing silicone oil is fixed at 0.1 g (b).

[0039] Fig.14 The contact angle changes of the finished fabrics at different modified CNCs contents (a) and different immersion times (b).

[0040] Fig.15 Are the images of self-cleaning (chalk powder (a1-a3) and methylene blue powder (b1-b3) ) and anti-staining test (c1-c3) of cotton fabric after finishing.

[0041] Fig.16 The superhydrophobic coated fabric oil-water mixture was used to separate n-heptane / water mixture (a1-a4) and carbon tetrachloride / water mixture (b1-b4); the coated fabric was used to remove the n-heptane (c1-c3) floating on the water surface and the carbon tetrachloride layer sinking to the bottom of the water.

[0042] Fig.17 The separation efficiency of oil-water separation after 10 cycles (a) and the relationship between the number of separations and the adsorption capacity of the finished cotton fabric after 40 separation cycles (b).

[0043] Fig.18 The WCA values ​​of the treated cotton fabric at pH=3 (a), pH=12 (b), 1M NaCl immersion time (c) and different pH values ​​(d). DETAILED DESCRIPTION

[0044] The present invention discloses a super-hydrophobic fabric, which provides surface roughening for modified cellulose nanocrystals and silicone oil to impart low surface energy, and the two work synergistically to provide super-hydrophobic function. The super-hydrophobic fabric of the present invention comprises fabric, cellulose nanocrystals grafted with hydrophobic segments, and low surface energy substances provided by silicone oil; the super-hydrophobic fabric is formed by the combined action of rough morphology and low surface energy substances. Silicon-based functional groups are introduced into the cellulose nanocrystals of the present invention during the modification process, and they have good compatibility with silicone oil in the treatment liquid, and when forming a roughened morphology, they also have good compatibility and interface bonding characteristics with the surface silicone oil film layer, so the process and application performance are excellent.

[0045] See also Figure 1 The present invention obtains the above-mentioned super-hydrophobic fabric through a simple immersion and drying strategy. First, cellulose nanocrystals are modified by silane, and then the modified cellulose nanocrystals are dispersed in an organic silicon treatment solution. The cellulose-based fabric is then immersed for a certain period of time and dried at a certain temperature to obtain the product.

[0046] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The raw materials involved are conventional commodities, and the raw cotton fabric is a hydrophilic fabric (100% desizing, see Figure 2 ), the hydrogen-containing silicone oil has a hydrogen content of 1.6%; the specific preparation operation and testing are conventional techniques, and the experiments are carried out in air unless otherwise specified.

[0047] Preparation of cellulose nanocrystals. The absorbent cotton was cut into small pieces of 2-5 mm, treated with 5% NaOH (w / w) aqueous solution for 4 h, and stirred at room temperature (the weight ratio of cotton to NaOH aqueous solution was 1:100). The treated cotton was then thoroughly washed with deionized water, repeated 5 times to ensure that the caustic soda was completely washed away and a neutral pH value was obtained. The washed cotton was then dried in an oven at 60 ° C overnight. Under 64% sulfuric acid hydrolysis conditions (acid ratio of 9 mL / g), the treatment temperature was maintained at 50 ° C and stirred for 2 h to investigate the effect of hydrolysis time on hydrolysis. The cotton and acid ratio was maintained at 1:20. 5 times water was used to dilute and stop the reaction, and maintained until the suspension was layered. The suspension at 8000 rpm was used as the raw material and centrifuged for 10 minutes. The collected sample was dialyzed in deionized water until neutral. Finally, the sample was freeze-dried at -60 ° C for 48 h to obtain cellulose nanocrystal powder.

[0048] Embodiment 1

[0049] Modification of cellulose nanocrystals. At room temperature, 2.8 g of heptadecafluorodecyltrimethoxysilane was added dropwise to a stirred 60 mL ethanol / water mixture (V (ethanol): V (water) = 9:1), and the pH was adjusted to 5 with glacial acetic acid. Then, the mixture was transferred to a reactor, 0.5 g of cellulose nanocrystal powder was added, and the mixture was stirred for 30 min. The mixture was heated to 85 °C and reacted for 6 hours under nitrogen protection. After the reaction, the precipitate after the reaction was collected by centrifugation and washed with ethanol. The washed product was centrifuged at 4000 r / min for 10 min, and the supernatant was removed to obtain a modified CNCs (F-CNCs) suspension (dispersion, solid content 4.95%, g / g). Figure 3 (a) is a scanning electron microscope (SEM) image of unmodified cellulose nanocrystals, and (b) is a scanning electron microscope (SEM) image of modified cellulose nanocrystals. The average particle size of the cellulose nanocrystals is 380 nm, and the average particle size after modification is 873 nm.

[0050] Preparation of super-hydrophobic fabric. 0.2 g of hydroxyl-terminated silicone oil (average molecular weight of 5000, viscosity of 100 cps), 0.1 g of hydrogen-containing silicone oil (average molecular weight of 2000, viscosity of 60 cps), and 0.01 g of dibutyltin dilaurate were completely dispersed in 50 mL of anhydrous isopropanol solution, and then 1 g of modified CNCs suspension was added and stirred to form a uniform dispersion. A 5 cm × 5 cm original fabric was immersed in the above dispersion for 15 s, then taken out and dried in an oven at 80 ° C for 10 min, and this process (immersion-drying) was repeated 2 times; the immersion process was carried out under normal stirring. Finally, the fabric dried for the third time was cured at 80 ° C for 1 h to obtain a super-hydrophobic fabric. Figure 4 This is a scanning electron microscope (SEM) image of cotton fabric after silicone oil finishing (addition of modified cellulose nanocrystals).

[0051] Contact angle test: The contact angle test of the finished cotton fabric was carried out using the DSA100 fully automatic microscopic droplet wettability measuring instrument produced by Krüss Company of Germany. Water was selected as the test droplet with a droplet volume of 5 μL. The test was performed 5 times and the average value was taken. Figure 5 is the water contact angle (WCA) value of cotton fabric after silicone oil finishing (adding modified cellulose nanocrystals). The water contact angle of the finished cotton fabric is 169.3° and the rolling angle is 4.9°, indicating that the modified cotton fabric has super hydrophobic properties.

[0052] EDS spectrum test. The components of the finished cotton fabric were analyzed by EDS spectrum. Figure 6The EDS element content and distribution diagram after finishing. The unfinished cotton fabric only contains C, O, and H elements, while the finished cotton fabric contains Si and F elements with percentage contents of 8.75% and 8.44%, respectively, which indicates that the modified cellulose nanocrystals are successfully attached to the fabric surface.

[0053] Sandpaper abrasion. The stability and fastness of the finished fabric are characterized by the sandpaper abrasion test. The sandpaper abrasion test method is as follows: cut the finished fabric to a suitable size, place the sample face down on 600-grit sandpaper, load a 100 g weight, clamp one end of the sample with tweezers and move it horizontally 100 mm, then return 100 mm to complete a wear cycle. Figure 7 This is the sandpaper abrasion contact angle of cotton fabric after silicone oil finishing (modified cellulose nanocrystals added). After 10 abrasion cycles, the hydrophobic angle is 167.1°. The relationship between the wettability of the coating and the number of times the tape is peeled off is shown by sticking the tape to the coating surface and applying a certain load. After ten adhesive tests, the contact angle decreased from 169.3° to 152.9°, and the superhydrophobicity was still maintained.

[0054] Fabric air permeability test. The air permeability of raw cotton and finished cotton fabrics was characterized using a fully automatic air permeability meter (YG461G). Test pressure: 200 Pa, test area: 20 cm 2 , caliber: 4Φ. Each sample was tested 5 times and the average value was taken. The average air permeability of the original cotton fabric used was 390.8mm / s, and the average air permeability of the finished cotton fabric was 348.8mm / s, which was only 10.7% lower than that of the untreated cotton fabric. While finishing the cotton fabric, it is hoped that the fabric will be given excellent superhydrophobicity and a certain mechanical fastness without affecting the wearing performance of the cotton fabric, so as to broaden the practical application of cotton fabric. The whiteness, stiffness and breaking strength of the finished fabric were tested. The whiteness of the raw cotton was 88.3%, and the whiteness of the finished cotton fabric was 88.8%. The whiteness before and after the finishing was almost unchanged, especially the impregnation finishing of the present invention had a very low effect on the air permeability of the fabric; the bending stiffness and breaking strength of the cotton fabric before and after the finishing were tested respectively. The flexibility of the raw cotton was 10.7 mm and the breaking strength was 391.38 mN / cm, and the corresponding results of the finished cotton fabric were 11.3 mm and the breaking strength was 492.4 mN / cm, both of which were increased. Therefore, the present invention improves the wearing performance of the cotton fabric by coating the cotton fabric.

[0055] The surface pores of the emulsion-finished fabric prepared by the prior art are reduced, and the channels for gas molecules to pass through the fabric are closed, resulting in a significant decrease in the air permeability of the fabric, with a decrease of 23%, and the whiteness is reduced from the initial 85.5% to 72.2%. The prior art uses nano-silicon dioxide particles (SNP) to improve the rough structure of the fabric surface, and introduces ethylenediaminetetraacetic acid (EDTA) to improve the durability of the super-hydrophobic fabric, and the air permeability of the prepared fabric is reduced by 50%. The prior art uses electrochemically driven hydrosol to directional in-situ deposit a uniform and dense film on the surface of the fabric, giving the cotton fabric super-hydrophobic properties. The hydrosol forms a hydrophobic film by electrochemical deposition, and the air permeability of the fabric after the final treatment is reduced by more than 20% compared with that before treatment. The prior art treats the cotton fabric with nano-TiO2, and then applies the hydrophobic organosilicon quaternary ammonium salt antibacterial agent to the fabric in a single-sided discontinuous printing mode, and prepares a single-sided super-hydrophobic fabric, which reduces the air permeability of the cotton fabric by 20%. By comparison, it can be seen that the air permeability of the super-hydrophobic fabric prepared by the present invention decreases very little.

[0056] Thermal performance test. TGA curve (heating rate of 10℃ / min, test atmosphere of nitrogen, temperature range of 30~600℃), the initial degradation temperature of raw cotton and coated fabric is almost maintained at around 320℃. The rapid decline in the quality of raw cotton fabric is because as the temperature rises, the crystallization area in the raw cotton fiber is destroyed, resulting in the production of intermediate products such as glucose, as well as gas. The final decomposition temperature is 437℃, and the corresponding residual carbon rate is 9.46%. The finished cotton fabric has a good thermal stability silicone oil composite structure membrane, which greatly improves the thermal stability of the cotton fabric. The thermodynamic curve of the finished cotton fabric shifts to the right, and the final degradation temperature is about 466℃, and the residual carbon rate is 11.30%. Compared with the raw cotton fabric, the residual carbon rate is improved and the stability is good.

[0057] The super-hydrophobic coating fabric was subjected to soap-resistant and friction-resistant tests and the change of the coating fabric's contact angle value to water was observed. When the washing cycle (standard synthetic detergent concentration 4 g / L, temperature 40°C, time 30 min per cycle, and 10 steel balls) reached 3 times, the water contact angle on the fabric surface decreased from 169.3° to 148.3°, only about 13% decrease, indicating that the coating fabric has good washability. After 2000 frictions using a friction-resistant fastness tester (YG571-II) different from sandpaper friction, the contact angle was still 153.7°, showing good durability.

[0058] Embodiment 2

[0059] Modification of cellulose nanocrystals. The heptadecafluorodecyltrimethoxysilane in Example 1 was replaced with 2.8 g of heptadecafluorodecyltriethoxysilane, and the rest was the same to obtain a modified CNCs (F-CNCs) suspension.

[0060] Preparation of super-hydrophobic fabric. 0.2g of hydroxy silicone oil (number average molecular weight of 3200, viscosity of 80cps), 0.1g of hydrogen silicone oil (number average molecular weight of 2000, viscosity of 60cps), and 0.01g of dibutyltin dilaurate were completely dispersed in 50 mL of anhydrous isopropanol solution, and then 1g of modified cellulose nanocrystal suspension was added and stirred to form a uniform dispersion. A 5 cm × 5 cm original fabric was immersed in the above dispersion for 15 s, then taken out and dried in an oven at 80°C for 10 min, and this process (immersion-drying) was repeated once; the immersion process should be carried out under stirring; the fabric dried for the second time was cured at 80°C for 1 h to obtain a super-hydrophobic fabric. Figure 8 This is a scanning electron microscope (SEM) image of cotton fabric after silicone oil finishing and addition of modified cellulose nanocrystals. Fig. 9 It is the water contact angle (WCA) value of cotton fabric after silicone oil finishing and adding modified cellulose nanocrystals. The water contact angle of the finished cotton fabric is 160° and the rolling angle is 9°, indicating that the modified finished cotton fabric has super hydrophobic properties.

[0061] Embodiment 3

[0062] Modification of cellulose nanocrystals. The heptadecafluorodecyltrimethoxysilane in Example 1 was replaced with 2 g of octadecyltrimethoxysilane, and the rest was the same to obtain a modified CNCs (F-CNCs) suspension.

[0063] Preparation of super-hydrophobic fabric: Referring to Example 1, the immersion-drying process was repeated 5 times, and the other processes were the same, and the fabric dried for the 6th time was cured at 80° C. for 1 h to obtain a super-hydrophobic fabric. Fig.10 is the water contact angle (WCA) value of cotton fabric after silicone oil finishing and adding modified cellulose nanocrystals. The water contact angle of the finished cotton fabric is 156°, indicating that the modified finished cotton fabric has hydrophobic properties.

[0064] Comparative Example 1

[0065] Preparation of super-hydrophobic fabric. Referring to Example 1, the modified cellulose nanocrystal suspension was omitted: 0.2 g of hydroxy silicone oil (number average molecular weight of 5000, viscosity of 100 cps), 0.1 g of hydrogen silicone oil (number average molecular weight of 2000, viscosity of 60 cps), and 0.01 g of dibutyltin dilaurate were completely dispersed in 50 mL of anhydrous isopropanol solution; a 5 cm × 5 cm original fabric was immersed in the above solution for 15 s, then taken out and dried in an oven at 80°C for 10 min, and this process (immersion-drying) was repeated 2 times; the immersion process was carried out under conventional stirring. Finally, the fabric dried for the third time was cured at 80°C for 1 h to obtain a hydrophobic fabric.

[0066] Fig.11 This is a scanning electron microscope (SEM) image of cotton fabric after silicone oil finishing. Fig.12 It is the water contact angle (WCA) value of cotton fabric after silicone oil treatment. The water contact angle of the treated cotton fabric is 140°.

[0067] Comparative Example 2

[0068] Modification of cellulose nanocrystals. The heptadecafluorodecyltrimethoxysilane in Example 1 was replaced with 2 g of phenyltrimethoxysilane, and the rest was the same to obtain a modified CNCs (F-CNCs) suspension.

[0069] Preparation of super hydrophobic fabric. Referring to Example 1, finally, the fabric dried for the third time was cured at 80°C for 1 h to obtain a hydrophobic fabric, and the water contact angle of the finished cotton fabric was 145°, indicating that the modified finished cotton fabric has hydrophobic properties.

[0070] Comparative Example 3

[0071] Preparation of super-hydrophobic fabric. Referring to Example 1, 1 g of the modified CNCs suspension was replaced with 0.05 g of cellulose nanocrystal powder (unmodified cellulose nanocrystal), and the rest was the same, and the fabric dried for the third time was cured at 80°C for 1 h to obtain a hydrophobic fabric, and the water contact angle of the finished cotton fabric was 141°.

[0072] Comparative Example 4

[0073] Preparation of super hydrophobic fabric: Referring to Example 1, only 0.3 g of terminal hydroxyl silicone oil was used, hydrogen-containing silicone oil was omitted, and the rest was the same, the fabric dried for the third time was cured at 80°C for 1 h to obtain a hydrophobic fabric, and the water contact angle of the cotton fabric after finishing was 131.3°.

[0074] Preparation of super hydrophobic fabric. Referring to Example 1, only 0.3 g of hydrogenated silicone oil was used, and the terminal hydroxyl silicone oil was omitted. The other conditions were the same, and the fabric dried for the third time was cured at 80°C for 1 h to obtain a hydrophobic fabric. The water contact angle of the cotton fabric after finishing was 142°. The fabric after finishing became hard and brittle, and lost its flexibility.

[0075] Embodiment 4

[0076] On the basis of Example 1, the amount of hydroxyl-terminated silicone oil (PHMS) and hydrogen-containing silicone oil (MSDS) was changed, and the rest was the same. The water contact angle of the obtained fabric was Fig.13 The fabric is finished by mixing hydrogen-containing silicone oil and terminal hydroxyl silicone oil in a certain proportion and dissolving them in isopropyl alcohol, forming a firm and flexible three-dimensional network structure film on the surface of the fiber, which significantly improves the hydrophobicity of the fabric.

[0077] On the basis of Example 1, the amount of the modified CNCs suspension was changed, and the rest was the same. The water contact angle of the obtained fabric was Fig.14 On the basis of Example 1, the number of immersion-drying times was changed, and the other aspects were the same. The water contact angle of the obtained fabric was Fig.14 Middle b.

[0078] Embodiment 5

[0079] The wettability of the super-hydrophobic coating fabric (Example 1) was evaluated by WCA value and WSA value test. The initial water contact angle of the super-hydrophobic coating fabric was 169.3°, and after standing for 5min, 10min, and 15min, the water contact angle still reached 168.2°, 166.1°, and 162.3°, proving that the coated fabric is not only super-hydrophobic but also has good water-repellent stability.

[0080] Embodiment 6

[0081] Take the coated fabric prepared by the method of Example 1 as an example.

[0082] In order to study the self-cleaning properties of cotton fabrics after finishing, methylene blue powder and chalk powder were used as pollutants. Fig.15 As shown, the super-hydrophobic coating fabric is fixed on the surface of the slide glass and tilted on the glass dish. Along with the dripping of water droplets, the pollutants attached to the fabric can be taken away as the water droplets roll off, and it can be clearly seen from the figure that the fabric surface is not stained by pollutants. In addition, the anti-fouling performance of the super-hydrophobic coating fabric is also tested, and the coated fabric is immersed in the water of methylene blue dyeing, then taken out from the water, and it is found that the fabric is not stained with blue stains. The above results show that the super-hydrophobic coating fabric prepared by the present invention has excellent self-cleaning and anti-fouling performance.

[0083] like Fig.16As shown, in order to measure the oil-water separation performance after fabric finishing. First, n-heptane and carbon tetrachloride are dyed with oil red to represent oils and organic solvents with densities less than and greater than water respectively. When the super-hydrophobic coating fabric contacts the n-heptane layer floating on the water surface, due to its excellent lipophilicity and the rough structure on the surface, the coating fabric can quickly absorb the n-heptane oil layer on the water surface. Similarly, the coated fabric is placed under the water surface with tweezers to contact the carbon tetrachloride oil layer, and the carbon tetrachloride can also be absorbed cleanly, and the excellent hydrophobicity makes the coated fabric no water droplets attached to it when it is taken out from the water. After finishing, the adsorption capacity of the fabric to carbon tetrachloride and n-heptane can reach 4.50 and 2.67 times of its own mass. At the same time, the repeated oil absorption and reuse performance of the coated fabric was studied, and it was confirmed that the super-hydrophobic coating fabric prepared by the present invention has good reuse. After 40 oil absorption-separation cycle experiments, the super-hydrophobic coating fabric has substantially no change in its absorption capacity for the oil phase, which indicates that the basic structure of the super-hydrophobic coating fabric has not been destroyed after 40 oil absorption-separation cycle experiments. At the same time, the coated fabric that has absorbed oil can be directly rinsed with ethanol and then dried, and can be reused. This shows that the coated fabric prepared by the present invention has practicality in the field of oil spills and water purification.

[0084] It is often not enough to directly immerse the coated fabric in the oil-water mixture to absorb the oil to achieve the purpose of oil-water separation. To separate a large amount of oil-water mixture, two-dimensional materials such as fabrics can be used to filter it. In this experiment, an oil-water separation device was used to evaluate the separation performance of the finished fabric. Fig.16 It can be seen that when 10 ml of deionized water dyed with methylene blue and 10 ml of oil phase dyed with oil red are placed in a measuring cylinder and injected into the oil-water separator, the oil droplets are quickly absorbed and collected in the conical flask below when they contact the coated fabric, while the water cannot penetrate and remains on the top of the coated fabric, thus achieving the separation of the oil phase and the water phase. In the experiment, two incompatible oil-water mixtures (n-heptane / water mixture and carbon tetrachloride / water mixture) were used to carry out the oil-water separation experiment. When the mixture of n-heptane and water is poured on the surface of the coated fabric, since the density of n-heptane is smaller than that of water, n-heptane is poured out of the measuring cylinder first, contacts and immediately wets the surface of the coated fabric, and quickly flows through the coated fabric, and the water is trapped above the coated fabric. Compared with the separation experiment of carbon tetrachloride / water mixture, the difference lies in the different order in which the water phase or oil phase is poured out of the measuring cylinder first. Carbon tetrachloride is denser than water, so the water phase first contacts the surface of the super-hydrophobic fabric and is retained. When carbon tetrachloride is poured on the surface of the super-hydrophobic fabric, the denser carbon tetrachloride will quickly pass through the water layer to contact the surface of the coated fabric and flow into the conical flask, and no water will pass through the surface. The hydrophobicity and lipophilicity of the super-hydrophobic coated fabric are the determining factors for the formation of oil-water separation. Fig.17As shown, after 10 separation cycles, the coated fabric still has a high separation efficiency, which can reach more than 99%, showing good oil-water separation performance and circulation capacity.

[0085] The chemical durability of the finished fabric is crucial to its practical application. Superhydrophobic fabrics often face the challenges of harsh environments in practical applications. The coated fabrics were tested in the WCA test using 5 μL of water droplets with different pH values ​​(ranging from 2 to 14). Fig.18 The results show that the coated fabric exhibits super hydrophobicity in the range of pH = 2 to 14, and the WCA values ​​are all greater than 150°. The coated fabric was treated with strong acid and strong base solutions of pH = 3 and 12 for 30 h, and the changes in the WCA value were measured to evaluate the long-term durability of the coated fabric. After 30 h of acid treatment, the WCA value of the coated fabric was still higher than 150°, and the hydrophobicity was still maintained. After 30 h of alkaline treatment, the WCA value of the coated fabric dropped to below 150°, but was still higher than 120°, which shows that the coated fabric still has hydrophobicity. After being treated with 1M NaCl solution for 30 h, the WCA also remained above 150°, still showing good hydrophobicity. This shows that the prepared coated fabric has good stability, and the above all strongly proves that the super hydrophobic coated fabric prepared by the present invention can be used in harsh environments.

[0086] The surface of the original cotton fabric has many gully-like structures and a certain roughness. At the same time, because of the hydrophilicity of the cotton fabric itself, when water droplets contact the fabric surface, the fabric will be quickly infiltrated. The surface of the fabric after silicone oil finishing becomes very smooth, and the fiber is covered with a layer of film. The hydrophobic angle of the fabric after silicone oil finishing can reach 140°, and there is no rolling angle, but it is not super-hydrophobic. The fabric finished by silicone oil containing modified CNCs in the present invention shows perfect super-hydrophobicity, with a contact angle of 169.3° and a rolling angle of 4.9±0.1°. Cellulose nanocrystals are fixed on the surface of the fiber. Due to the effects of covalent bonds, van der Waals forces and hydrophobic forces, many nanoparticles are condensed together. The coated fabric was tested for oil-water separation. After ten oil-water separation cycles, the separation efficiency can still reach more than 99%. After the fabric was treated with acid (pH=3), alkali (pH=13), and 1M NaCl for 30 h, rubbed with sandpaper 50 times, adhered with tape 10 times, rubbed with a friction fastness meter 2000 times, and washed with soap for 3 cycles, it still had good hydrophobic properties, showing excellent stability and cyclic ability. At the same time, superhydrophobic fabrics also have good application prospects in the fields of self-cleaning, anti-fouling, oil absorption, and oil-water separation.

Claims

1. A super hydrophobic fabric, comprising a fabric and a surface finishing layer thereof, characterized in that: The preparation method of the super-hydrophobic fabric comprises the following steps: dispersing modified cellulose nanocrystals in an organic silicon treatment solution to obtain a solution containing modified cellulose nanocrystals and organic silicon; the organic silicon treatment solution comprises hydrogen-containing silicone oil, terminal hydroxyl silicone oil, a solvent and a catalyst; immersing the fabric in the solution containing modified cellulose nanocrystals and organic silicon, then taking it out and drying it to obtain the super-hydrophobic fabric; the modified cellulose nanocrystals are fluorine-containing silane-modified cellulose nanocrystals or non-fluorine-containing silane-modified cellulose nanocrystals; the fluorine-containing silane comprises tridecafluorooctyltrimethoxysilane, One or more of tridecafluorooctyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, and heptadecafluorodecyltriethoxysilane; the fluorine-free silane includes one or more of octadecyltrimethoxysilane, octadecyltriethoxysilane, hexadecyltrimethoxysilane, and hexadecyltriethoxysilane; the mass ratio of terminal hydroxyl silicone oil to hydrogen-containing silicone oil is (1-2):1; the amount of modified cellulose nanocrystals, hydrogen-containing silicone oil and terminal hydroxyl silicone oil and the volume ratio of solvent are (0.03-0.06)g: (0.2-0.4)g:50mL.

2. The super hydrophobic fabric according to claim 1, characterized in that: The fabric includes cotton, linen, regenerated cellulose fiber-based fabric or a blended fabric of any two of the above.

3. The method for preparing the super hydrophobic fabric according to claim 1, characterized in that: The modified cellulose nanocrystals are dispersed in an organosilicon treatment liquid to obtain a solution containing the modified cellulose nanocrystals and organosilicon; the organosilicon treatment liquid includes hydrogen-containing silicone oil, terminal hydroxyl silicone oil, a solvent and a catalyst; the fabric is immersed in the solution containing the modified cellulose nanocrystals and organosilicon, and then taken out and dried to obtain the super-hydrophobic fabric.

4. The method for preparing a super hydrophobic fabric according to claim 3, characterized in that: The solvent is any one or more of methanol, ethanol and isopropanol; the catalyst is one of dibutyltin dilaurate, tin acetylacetonate and manganese acetylacetonate; the amount of the catalyst accounts for 1% to 5% of the total mass of the silicone oil.

5. The method for preparing a super hydrophobic fabric according to claim 3, characterized in that: The number of immersions is 1 to 10 times, and the number of dryings is 1 to 10 times.

6. Use of the super hydrophobic fabric according to claim 1 in preparing flexible hydrophobic materials.

Citation Information

Patent Citations

  • Hydrophobic modification method of nanocellulose

    CN107383212A

  • Preparation method of nanofiber super-hydrophobic coating

    CN112111198A